2021
DOI: 10.1021/acs.jafc.0c08085
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Luteolin: A Narrative Review Focusing on Its Pharmacokinetic Properties and Effects on Glycolipid Metabolism

Abstract: Luteolin, a flavone subclass of flavonoids, is commonly found in food plants and has multiple biological activities. Recently, evidence is growing with regard to the potential of luteolin intake to beneficially affect glycolipid metabolism disorders (GLMDs), particularly insulin resistance, diabetes, and obesity. The aim of this contribution is to provide an overview of recent advances in identifying and understanding the pharmacokinetic properties (absorption, metabolism, and bioavailability) of luteolin, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 133 publications
3
57
0
1
Order By: Relevance
“…As previously discussed ( 23), Erlund et al (24) demonstrated that the Tmax of oral quercetin aglycone in healthy humans ranged from 1.9±1.2 to 4.9±2.1 h in a dose-dependent manner, and Graefe et al (25) demonstrated that the Tmax of oral quercetin glycosides in humans was 0.7±0.2 to 0.3 h. Lee and Mitchell (26) reported that the Tmax of dietary quercetin from onion powder and apple peel powder was 2.0±1.7 and 2.9±2.0 h in humans, respectively. To the best of our knowledge, there are no studies available to date on the pharmacokinetics of luteolin in humans; however, oral luteolin in rats is known to be absorbed efficiently with a Tmax of 1.1 h (27,28). Yasuda et al (29) also demonstrated that blood luteolin levels rapidly increased at 0.5 h following the oral ingestion with a Tmax of 1.0 h, as also previously discussed (27).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As previously discussed ( 23), Erlund et al (24) demonstrated that the Tmax of oral quercetin aglycone in healthy humans ranged from 1.9±1.2 to 4.9±2.1 h in a dose-dependent manner, and Graefe et al (25) demonstrated that the Tmax of oral quercetin glycosides in humans was 0.7±0.2 to 0.3 h. Lee and Mitchell (26) reported that the Tmax of dietary quercetin from onion powder and apple peel powder was 2.0±1.7 and 2.9±2.0 h in humans, respectively. To the best of our knowledge, there are no studies available to date on the pharmacokinetics of luteolin in humans; however, oral luteolin in rats is known to be absorbed efficiently with a Tmax of 1.1 h (27,28). Yasuda et al (29) also demonstrated that blood luteolin levels rapidly increased at 0.5 h following the oral ingestion with a Tmax of 1.0 h, as also previously discussed (27).…”
Section: Discussionmentioning
confidence: 69%
“…To the best of our knowledge, there are no studies available to date on the pharmacokinetics of luteolin in humans; however, oral luteolin in rats is known to be absorbed efficiently with a Tmax of 1.1 h (27,28). Yasuda et al (29) also demonstrated that blood luteolin levels rapidly increased at 0.5 h following the oral ingestion with a Tmax of 1.0 h, as also previously discussed (27). As regards these data on oral bioavailability and Tmax, the current setting of blood sampling (1 h following JHQGG ingestion) was considered to be appropriate for the pilot study of the acute immunological effects of JHQGG.…”
Section: Discussionmentioning
confidence: 99%
“…Luteoloside or cynaroside, commonly known as luteolin-7-glucoside, is another flavonoid found in many plants and herbs. It, together with its metabolites, has been described as an antioxidant, glycolipid balancing, neuroprotective, hepatic metabolism homeostasis, antiobesity, antidiabetic, cardioprotective, and cholesterol-level maintenance agent [ 122 ]. The involvement of the PPAR/Nrf2/ NF-κB signaling pathway in attenuating neuroinflammation in localized cerebral ischemia in rats was discovered by Li et al [ 117 ].…”
Section: Natural Compounds As Ppar Agonistsmentioning
confidence: 99%
“…Luteolin (3′,4′,5,7-tetrahydroxyflavone) is a flavone that has been serving as a supplemental nutrient for decades for improving memory and brain health ( Swaminathan et al, 2019 ; Wang et al, 2021 ). Luteolin can protect heart from damage caused by over-produced ROS and over-loaded calcium ( Wang et al, 2012 ; Yan et al, 2018 ).…”
Section: Natural Flavones Exhibit Potential In Treating Hf Via Dual Regulation Of Calcium and Rosmentioning
confidence: 99%